Gasoline Direct Injection Engine Emissions of OC and EC: Laboratory Comparisons with Port Fuel Injection Engine - Jie Zhang; John Liggio; Tak W. Chan; Lin Huang; Jeffrey R. Brook (Aerosol and Air Quality Research)
Abstract To better understand carbonaceous aerosol emissions from gasoline vehicles, a gasoline direct injection (GDI) vehicle with and without a gasoline particle filter (GPF) installed and a port fuel injection (PFI) vehicle were tested on a chassis dynamometer using standard emission drive cycles. Carbonaceous particles emitted from the vehicles were collected on quartz filters and analyzed using three different thermal optical protocols to assess the sensitivity of organic carbon (OC) and elemental carbon (EC) emission estimates to the methods, showing OC obtained by the IMPROVE and EC by the NIOSH protocol was the lowest. Compared to the PFI vehicle, the GDI vehicle had higher EC and OC emissions under cold-start cycles by 1415% and 46%, respectively. However, the OC emission from the PFI vehicle was higher than GDI during an aggressive driving cycle by 146%. By considering OC collected on a quartz filter behind a Teflon filter, the emissions from PFI vehicle were found to be more volatile than the GDI vehicle. This is consistent with the OC forming characteristics for GDI and PFI engines, which are pyrolyzed particles from incomplete combustion and incomplete volatilization of fuel droplets, respectively. Generally, the particle phase OC emissions from gasoline engines are more volatile than other sources (e.g., biomass burning), supported by the very low level of pyrolyzed organic carbon (POC) and small differences among protocols in the current study. Once the GDI vehicle was equipped with a GPF, the removal efficiency of EC was > 98%, but OC emissions could increase as a result of regeneration, suggesting that the effect of a GPF on total carbon emitted to the atmosphere needs further evaluation, especially considering the formation of secondary organic aerosol.